Identification of the propagation mode of a solar wind wave associated with Pc5 pulsations in the magnetosphere - A. D. M. Walker; J. A. E. Stephenson (Annales Geophysicae, 2014)
A case study of a magnetohydrodynamic (MHD) wave in the solar wind that is strongly correlated with a magnetospheric field line resonance observed by the SuperDARN (Super Dual Auroral Radar Network) radar at Sanae, Antarctica is presented. The data from the ACE (Advanced Composition Explorer) satellite at the solar libration point are analysed. The data time series are bandpass filtered at the pulsation frequency and the analytic signal deduced. From these data the partition of energy between the field components is computed. It is shown that energy is equally partitioned between the kinetic energy and transverse magnetic potential energy densities. The energy flux vector is closely aligned with the background magnetic field. The transverse magnetic and velocity components are in antiphase. This is the first identification of the triggering wave as a transverse Alfvén wave which originates upstream from the space craft and is propagated to the magnetosphere to trigger the pulsation.